Clinical Assisted Reproduction: Cumulus Cell Contribution to Cytoplasmic Maturation and Oocyte Developmental Competence In Vitro - Hassan, Hassan Aly (Kluwer Academic Publishers-Plenum Publishers, 2001)
Objective: Although several reports indicated the bidirectional communication between the oocyte and granulosa cell, and the potential negative impact of premature cumulus removal, clinical data are controversial. The present analysis report the results of a prospective randomized study done on sibling oocytes to evaluate whether or not preincubation with intact cumulus is needed in ICSI. Methods: It was a prospective randomized study, and conducted at Alexandria IVF–ICSI center. This study was performed using 926 M2 oocytes from 141 cycles of patients undergoing ICSI. Oocytes were randomized between three protocols: protocol A (immediate denudation, immediate injection), protocol B (delayed denudation, delayed injection), and protocol C (early denudation, delayed injection). Main outcome measure(s) were maturation, fertilization, and cleavage rate after ICSI. Results: Aspects of nuclear, cytoplasmic maturation and oolemma properties were improved when oocytes were preincubated with intact cumulus before ICSI. Conclusions: Preincubation, before ICSI improved results. Duration of preincubation should be program specific.